The Soviet Influence: Battleship Potemkin & Drifters - Meisel, Edmund (BFI, 2012)
In the 1920s and 1930s, Soviet propaganda films profoundly influenced the emerging luminaries of British documentary filmmaking. Sergei Eisenstein's groundbreakin "Battleship Potemkin" was not seen in the UK until the momentous London Film Society screening in 1929, where it was double-billed with John Grierson's "Drifters". [Cover]